Renewable energy and the role of molten salts and carbon - Fray D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Molten carbonate fuel cells have been under development for a number of years and reliable units are successfully working at 250kW scale and demonstration units have produced up to 2 MW. Although these cells cannot be considered as renewable as the fuel, hydrogen or carbon monoxide is consumed and not regenerated, the excellent reliability of such a cell can act as a stimulus to innovative development of similar cells with different outcomes. Molten salt electrolytes based upon LiCl - Li2O can be used to convert carbon dioxide, either drawn from the output of a conventional thermal power station or from the atmosphere, to carbon monoxide or carbon. Recently, dimensionally stable anodes have been developed for molten salt electrolytes, based upon alkali or alkaline ruthenates which are highly electronically conducting and these may allow the concept of high temperature batteries to be developed in which an alkali or alkaline earth element reacts with air to form oxides when the battery is discharging and the oxide decomposes when the battery is being recharged. Batteries using these concepts may be based upon the Hall-Heroult cell, which is used worldwide for the production of aluminium on an industrial scale, and could be used for load levelling. Lithium ion batteries are, at present, the preferred energy source for cars in 2050 as there are sufficient lithium reserves to satisfy the world’s energy needs for this particular application. Graphite is used in lithium ion batteries as the anode but the capacity is relatively low. Silicon and tin have much higher capacities and the use of these materials, encapsulated in carbon nanotubes and nanoparticles will be described. This paper will review these interesting developments and demonstrate that a combination of carbon and molten salts can offer novel ways of storing energy and converting carbon dioxide into useful products.